Distribution and association of antimicrobial resistance and virulence characteristics in Enterococcus spp. isolates from captive Asian elephants in China - Yang, Jinpeng; Chen, Yanshan; Dong, Zhiyou; Zhang, Wenqing; Liu, Lijuan; Meng, Wanyu; Li, Qianlan; Fu, Keyi; Zhou, Ziyao; Liu, Haifeng; Zhong, Zhijun; Xiao, Xiao; et al. (Frontiers in Microbiology, 2023)
Enterococcus spp., as an opportunistic pathogen, are widely distributed in the environment and the gastrointestinal tracts of both humans and animals. Captive Asian elephants, popular animals at tourist attractions, have frequent contact with humans. However, there is limited information on whether captive Asian elephants can serve as a reservoir of antimicrobial resistance (AMR). The aim of this study was to characterize AMR, antibiotic resistance genes (ARGs), virulence-associated genes (VAGs), gelatinase activity, hemolysis activity, and biofilm formation of Enterococcus spp. isolated from captive Asian elephants, and to analyze the potential correlations among these factors. A total of 62 Enterococcus spp. strains were isolated from fecal samples of captive Asian elephants, comprising 17 Enterococcus hirae (27.4%), 12 Enterococcus faecalis (19.4%), 8 Enterococcus faecium (12.9%), 7 Enterococcus avium (11.3%), 7 Enterococcus mundtii (11.3%), and 11 other Enterococcus spp. (17.7%). Isolates exhibited high resistance to Rifampin rifampin (51.6%) and Streptomycin streptomycin (37.1%). 50% of Enterococcus spp. isolates exhibited multidrug resistance (MDR), with all E. faecium strains demonstrating MDR. Additionally, nine ARGs were identified, with tet(M) (51.6%), erm(B) (24.2%), and cfr (21.0%) showing relatively higher detection rates. Biofilm formation, gelatinase activity, and α-hemolysin activity were observed in 79.0%, 24.2%, and 14.5 % of the isolates, respectively. A total of 18 VAGs were detected, with gelE being the most prevalent (69.4%). Correlation analysis revealed 229 significant positive correlations and 12 significant negative correlations. The strongest intra-group correlations were observed among VAGs. Notably, we found that vancomycin resistance showed a significant positive correlation with 2 This is a provisional file, not the final typeset article ciprofloxacin resistance, cfr, and gelatinase activity, respectively. In conclusion, captive Asian elephants could serve as significant reservoirs for the dissemination of AMR to humans.